1997
DOI: 10.1021/bi970049q
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dynamical Properties of a Denatured Protein. Heteronuclear 3D NMR Experiments and Theoretical Simulations of Lysozyme in 8 M Urea

Abstract: Oxidized and reduced hen lysozyme denatured in 8 M urea at low pH have been studied in detail by NMR methods. 15N correlated NOESY and TOCSY experiments have provided near complete sequential assignment for both 1H and 15N resonances. Over 900 NOEs, including 130 (i, i + 2) and 23 (i, i + 3) NOEs, could be identified by analysis of the NOESY spectra of the denatured states, and 3J(HN, Halpha) coupling constants and 15N relaxation rates have been measured. The coupling constant and NOE data were analyzed by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
401
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(437 citation statements)
references
References 66 publications
34
401
1
1
Order By: Relevance
“…It is not possible therefore to provide a picture of a unique conformation for this peptide in solution, nor is it meaningful to do so. A complete description of the glycopeptide would have to take into account in detail the conformational averaging, and would involve an ensemble approach such as recently described for denatured lysozyme (Schwalbe et al, 1997). However, because the ATPA subsequences do have a preferred conformation, it is useful to focus on them, as it is possible that the disaccharide moiety interacts with the ice crystal or membrane surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not possible therefore to provide a picture of a unique conformation for this peptide in solution, nor is it meaningful to do so. A complete description of the glycopeptide would have to take into account in detail the conformational averaging, and would involve an ensemble approach such as recently described for denatured lysozyme (Schwalbe et al, 1997). However, because the ATPA subsequences do have a preferred conformation, it is useful to focus on them, as it is possible that the disaccharide moiety interacts with the ice crystal or membrane surface.…”
Section: Discussionmentioning
confidence: 99%
“…The NOESY spectrum shows that the NH of the acetamide side chain of the GalNac residues has a large coupling constant (3J > (Wuthrich, 1986;Schwalbe et al, 1997). However, the rate of exchange of the Ala NH with water, as observed in the ROESY spectrum, is for most residues considerably greater than for the threonine residues, or the NHAc in the GalNAc residues.…”
Section: An Lane Et Almentioning
confidence: 97%
“…In both its nonphosphorylated and phosphorylated states, the R region has R 2 relaxation rates generally in the range of 4-8 s -1 , consistent with the values expected for a disordered protein and lower than those expected for a folded protein with the same number of residues. Uniformly low R 2 relaxation rates throughout the sequence, with further reduced rates at the termini, are expected for a model disordered protein with no structural contacts 29 . In contrast, the R 2 relaxation rates for the R region are not uniform throughout the sequence: higher rates were observed for a number of residues, including His667, Glu733, Ser768 and Ser809, that are within regions having >5% helical population and close to phosphorylation sites.…”
Section: Phosphorylation Reduces R-region Structural Contactsmentioning
confidence: 97%
“…In contrast, the R 2 relaxation rates for the R region are not uniform throughout the sequence: higher rates were observed for a number of residues, including His667, Glu733, Ser768 and Ser809, that are within regions having >5% helical population and close to phosphorylation sites. This suggests that the restriction of motion by secondary structural contacts contributes to higher R 2 relaxation rates, with potential additional contributions from the exchange of individual conformers between different conformational states, tertiary contacts or hydrophobic clusters 29 . Phosphorylation generally decreases R 2 relaxation rates (see difference between …”
Section: Phosphorylation Reduces R-region Structural Contactsmentioning
confidence: 97%
“…29,31,32 Surprisingly, measurements performed on the IDP α-synuclein also showed a small dispersion at ωτ R = 1 with a correlation time comparable to the reorientation time calculated for a folded protein with the same molecular weight. 29 The dispersion should not be observed if α-synuclein was only subject to segmental motions with correlation times much shorter than the reorientation time of the protein, 16,33 since the dispersions corresponding to such times occur at much larger fields. The observed dispersion therefore suggested that a residual correlated motion is present in α-synuclein.…”
Section: ■ Introductionmentioning
confidence: 99%